"A Modified Method for Preparation of Staphylococcus aureus Peptidoglycan Towards Making a Sub – Unit Vaccine" - F Esmaily; MK Sharifi–Yazdi (Iranian Journal of Public Health, 2002)
The immounological responses to S. aureus cell wall antigens, namely crude or whole cell, teichoic acid (TA) peptidoglycan prepared in conventional way (CPG), cell wall (CW), lipoteichoic acid (LTA) were investigated by number of immunological methods e.g. RIA, ELISA, immunodiffusion and western blotting techniques.Also a method for preparation of peptidoglycan (MPG) was modified and used as vaccine for our protection studies. In general the responses in rabbits (serum titre) to fractions of S. aureus, varied, crued antigen showed the highest end-point titer while lipoteichoic acid showed the lowest end-point. The highest end-point titre was always seen between homologous sera and antigens. Modified pepdidoglycan and cell wall (PG + TA) showed the similar titre against S. epidermidis hyperimmueserum. The cross – reactivty was also seen between fractions by S. aureus Bate . S. aureus Wood (lack protein A) S. epidermidis and streptococci against various immune sera tested by Elisa and gel diffiusion. The results demonstrated that protective antibody can be obtained between different strain or species of bacteria due to the presence of common antigen or antigenes especially PG in gram - positive bacteria.